2014
DOI: 10.1016/j.chom.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A Type VI Secretion-Related Pathway in Bacteroidetes Mediates Interbacterial Antagonism

Abstract: Summary Bacteroidetes are a phylum of Gram-negative bacteria abundant in mammalian-associated polymicrobial communities, where they impact digestion, immunity and resistance to infection. Despite extensive competition at high cell density that occurs in these settings, cell contact-dependent mechanisms of interbacterial antagonism, such as the type VI secretion system (T6SS), have not been defined in this group of organisms. Herein we report the bioinformatic and functional characterization of a T6SS-like path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
292
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(306 citation statements)
references
References 67 publications
5
292
0
2
Order By: Relevance
“…The human gut symbiont B. fragilis N (13) effectively kills the T6SS -human gut commensal Bacteroides thetaiotaomicron in a T6S-dependent manner in vitro (11). Whether B. fragilis N also targets B. thetaiotaomicron in the gut is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The human gut symbiont B. fragilis N (13) effectively kills the T6SS -human gut commensal Bacteroides thetaiotaomicron in a T6S-dependent manner in vitro (11). Whether B. fragilis N also targets B. thetaiotaomicron in the gut is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…2). Because numerous human gut Bacteroidetes besides B. fragilis carry T6SS loci (11,12,15), additional effectors will be readily identifiable in other species. These effectors reveal strategies human gut symbionts themselves have evolved to target other members of this community, and may provide important new approaches for precision microbiome manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In collaboration with Andrew Goodman's group, she specifically showed that Bacteroidetes are equipped with a surprisingly high diversity of anti-bacterial toxins that are involved in maintaining the symbiotic relationship with the mammalian gut. 23 …”
Section: Session 1: Inter-bacterial Communication Exchange and Compementioning
confidence: 99%